'It's not getting them the support they need': Exploratory research of police officers' experiences of community mental health. (December 2019) - Lamb, Vicky; Tarpey, Emma
Police officers are first responders in a role which not only encompasses crime, but also increasing welfare issues. Issues have been highlighted with officers 'detaining' those with mental health difficulties and the impact that this process can have upon all involved. However, there appears to be a shift towards a police-health nexus. An exploratory study interviewed ten UK police officers with a view to understanding officers' experiences of working with people with mental health difficulties and the availability of training for this role. With increasing demands to support people with mental health concerns, alongside a reduction in officer numbers, thematic analysis highlighted three themes: Support, Impact on the Officer and Understanding Mental Health. Increasing demands, a lack of training and limited multi-agency working were experienced by officers. However, officer-to-officer support was strong. Recommendations are made to increase collaborative multi-agency working and review the role of police officers as first responders in mental health crises.